2019
DOI: 10.3390/met9070750
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Iron Whiskers during Gaseous Reduction of Hematite Iron Ore Fines

Abstract: A high-temperature confocal scanning laser microscope and an online reduction–water quenching experiment system were used to systematically study the generation of iron whiskers during the reduction of hematite ore particles with CO/CO2 gas. The "blooming" phenomenon of the surface during the reduction of iron ore particles was found in this experiment. The orientation of the grain on the longitudinal section of an iron whisker was measured to be uniform by applying the electron back-scattered diffraction tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the reduced sample after the experiment, iron formed an outer layer of the particles; this migration of iron from the particle core to the outside layer has been reported previously . A single titanium-free iron oxide and pure silicon oxide particle were detected; see the green and orange circles.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the reduced sample after the experiment, iron formed an outer layer of the particles; this migration of iron from the particle core to the outside layer has been reported previously . A single titanium-free iron oxide and pure silicon oxide particle were detected; see the green and orange circles.…”
Section: Resultssupporting
confidence: 80%
“…In the reduced sample after the experiment, iron formed an outer layer of the particles; this migration of iron from the particle core to the outside layer has been reported previously. 36 A single titanium-free iron oxide and pure silicon oxide particle were detected; see the green and orange circles. The area within the violet circle, which is attached to the oxygen carrier particle, showed high intensities of sodium, aluminum, silicon, and calcium and an even higher intensity of oxygen compared to that in the other particles.…”
Section: Resultsmentioning
confidence: 99%
“…The elements detected in the ash were mainly silicon and calcium. Iron seemed to form a layer on the iron sand particle's surface, which suggested that iron would migrate to the outer layer during highly reducing environments where it most likely formed wüstite [45]. A similar outward migration of iron was also seen in a sample investigated with gaseous…”
Section: Surface Morphology and Elemental Distribution Of Iron Sandmentioning
confidence: 65%
“… 38 At lower mass conversion degrees, another reaction may take place, and this implies a different reaction mechanism. For instance, the outward migration of iron phases to the particle surface during reduction 49 creates a chemically distinct iron layer, 50 which implies formation of the Fe/FeO interface. 15 , 51 As a result, the diffusion rate of fuel into the particle becomes much slower, so the reaction is likely controlled by diffusion at this stage.…”
Section: Resultsmentioning
confidence: 99%